Innovative Method for Ship Navigation Safety Risk Response in Landslide-Induced Wave - Peiyin Yuan; Pingyi Wang; Yu Zhao (Advances in Civil Engineering)
When the bank of a reservoir slope slides along a weak structural plane at a high speed, “landslide slamming” will occur in the nearby water. The formation of landslide-induced waves is a serious threat to the safety of wharfs, shore marks, buildings in the water, and vessels navigating in reservoir areas. To ensure the safety of navigating ships, this study proposes a landslide-induced wave water ship navigation safety risk response technology. The propagation characteristics of landslide-induced waves are analysed based on a physical model experiment, and the characteristics of a ship's motion response and mooring cable tensions are studied under conditions of bow and stern mooring and multipoint mooring. The influences of the landslide-induced wave direction and ship navigation position on the ship rolling motion characteristics are discussed. The results of this study can further improve the navigation safety of ships in landslide-induced wave waters.